Dynamics of Brexit Negotiations from the European Union 2016-2020 Period - Ma'arif, Hilman Mahmud Akmal; Rahmawati, Baiq Ulva; Sahide, Ahmad (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2023)
This article discusses the dynamics of negotiating Britain's exit from the EU or Brexit. Negotiations between the UK and the EU took a long time, from the leadership of PM Theresa May to PM Boris Johnson. During Theresa May's time, Brexit efforts failed to materialize and succeeded under Boris Johnson who dared to maneuver by ignoring the parliament. This study uses a qualitative method using negotiation theory and the concept of national interest. Sources of data obtained through e-books, news, journals from Scopus and Google Scholar. The findings of this study are traceable causes, actors and parties involved during the negotiation process occurs. In addition, one of the reasons the UK wants to leave the EU is the reluctance of the EU to control its domination over the UK in domestic activities, in terms of the economy and the policy of free movement of workers.